THE REASONS OF DIFFERENTIAL WALL STICKING IN DRILLING OIL AND GAS WELLS - Nalivaiko О.; Nalivaiko, L.; Reznichenko, A.; Chyhyriov, V. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Of the article raised the question of occurrence the causes of differential wall sticking. An attempt to analyze the mechanism of differential wall sticking in drilling oil and gas wells was made. Operations in liquidation of wall sticking and casing pipe that occur in drilling are the most difficult and time-consuming. One of the ways to improve the requirements ofcasing string cementing is the use of different chemical additives in cement that change the structure of well cement. One of them is hydrophobic additive «Silpan-Р», which effectiveness is described in the article. Own view on the issue of process occurrence of differential wall sticking that is different from the existing ones was offered. Keywords: drill string, differential sticking, osmosis, hydrophobic additive «Silpan-Р», well, pressure.